The potential for Gracilaria polyculture at Jacobs Bay Sea Products Pty - Morgan, Derek (Department of Biological Sciences, 2017)
This report investigates the potential for the culture of G. gracilis, an indigenous red alga, into the west coast mariculture farm Jacobs Bay Sea Products Pty. Various methods for cultivating Gracilaria as well as environmental parameters, which influence growth of Gracilaria, are disltussed below. From these optimal conditions for the polycultivation of G. gracilis are determined. Cultivation can take place either, in open waters, or on land. Open water systems are generally less intensive than land based operations. Open water systems can be either bottom planted or suspended. Suspended cultivation has the advantage of maintaining the plant thalli in optimal light intensities. Land based systems can make use of ponds, raceways or tanks. Tanks and raceways are more productive than ponds, but require higher ﬂow rates and regulated nutrient regimes.